Self-Governance and Reform in Kant’s Liberal Republicanism - Ideal and Non-Ideal Theory in Kant’s Doctrine of Right - Varden, Helga (DoisPontos, 2016)
At the heart of Kant’s legal-political philosophy lies a liberal, republican ideal of justice understood in terms of private independence (non-domination) and subjection to public laws securing freedom for all citizens as equals. Given this basic commitment of Kant’s, it is puzzling to many that he does not consider democracy a minimal condition on a legitimate state. In addition, many find Kant ideas of reform or improvement of the historical states we have inherited vague and confusing. The aim of this paper is to untangle both puzzles by exploring Kant’s idea of self-governance. I argue that Kant’s idea of self-governance gives us a very good starting point for thinking about how to leave room for a variety of political systems—different ideals—that have grown out of and responding to different contingent historical and cultural circumstances. It also helps us id entify those areas where we want to take extra care to build in safeguards to secure stability and to take sufficiently seriously humankind’s truly nasty sides. Autogovernança e Reforma no Republicanismo Liberal de Kant - Teoria Ideal e Não-Ideal na Doutrina do Direito em Kant No centro da filosofia jurídico-política de Kant está um ideal liberal, republicano de justiça compreendido em termos de independência privada (não-dominação) e sujeição às leis públicas que garantem a liberdade para todos os cidadãos como iguais. Dado este compromisso básico de Kant, é intrigante para muitos que ele não considere a democracia uma condição mínima para um Estado legítimo. Além disso, muitos consideram as idéias de Kant quanto à reforma ou melhoria dos estados históricos que herdamos, vagas e confusas. O objetivo deste artigo é desembaraçar os dois quebra-cabeças explorando a ideia de auto-governança de Kant. Eu argumento que a ideia de auto-governança de Kant nos dá um bom ponto de partida para pensar em como deixar espaço para uma variedade de sistemas políticos — diferentes ideais — que cresceram e responderam a diferentes contingências históricas e circunstâncias culturais. Também nos ajuda a identificar as áreas em que queremos ter um cuidado extra para construir salvaguardas para garantir a estabilidade segura e para levar suficientemente a sério os lados verdadeiramente desagradáveis da humanidade.